Epizootiological and Epidemiological Situation on Highly Pathogenic Avian Influenza Globally and in the Russian Federation in 2024 - N. N. Vasiltsova; A. S. Panova; V. N. Petrov; A. V. Danilenko; K. N. Shadrinova; S. V. Svyatchenko; K. I. Ivanova; G. S. Onkhonova; N. I. Goncharova; V. Yu. Marchenko (Проблемы особо опасных инфекций, 2025)
The aim of the work was to analyze the circulation of the most epidemiologically significant variants of the avian influenza virus in the world and across Russia in 2024. The global situation on highly pathogenic avian influenza remained tense in 2024. The disease affected 68 countries, resulting in the death or culling of about 19 million poultry. In addition, there was a large number of influenza A(H5N1) virus detections in wild and domestic mammals, predominantly in the United States. Those included outbreaks on dairy farms that affected herds throughout the year, encompassing more than 900 dairy farms in 16 states by the year’s end and causing infection of 40 farm workers in four states. The A(H5N1) viruses detected in farm workers contained mammalian adaptation mutations. In total, more than 100 human infections with zoonotic variants of influenza virus were reported in 2024, with influenza A(H5N1) virus detected in 81 cases. Apart from outbreaks of A(H5N1), other influenza virus variants, such as A(H5N6), A(H5N8), A(H5N5), A(H5N2), were circulating worldwide. Outbreaks among poultry caused by different subtypes of influenza A(H7) virus were also reported in a number of countries. In Russia, the situation on highly pathogenic influenza virus in 2024 was less tense. All detected influenza A(H5N1) viruses belonged to clade 2.3.4.4b and were genetically similar to the vaccine strains recommended by WHO. Isolated strains were antigenically similar to a reference strain A/goose/Tyumen/359- 13/2021(H5N1), which had HA1 sequence identical to the vaccine strain A/Astrakhan/3212/2020(H5N8). In addition, an influenza A(H9N2) virus was isolated in 2024. The study of this strain showed that it belongs to the clade Y439 and does not contain mutations associated with increased pathogenicity and drug resistance.